2013
DOI: 10.1029/2012jd017937
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric ozone and the morphology of the northern hemisphere planetary waveguide

Abstract: [1] A middle atmosphere general circulation model is used to examine the effects of zonally asymmetric ozone (ZAO) on the Northern Hemisphere planetary waveguide (PWG) during winter (December-February). The morphology of the PWG is measured by a refractive index, Eliassen-Palm flux vectors, the latitude of the subtropical zero wind line, and the latitude of the subtropical jet. ZAO causes the PWG to contract meridionally in the upper stratosphere, expand meridionally in the lower stratosphere, and expand verti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 57 publications
(113 reference statements)
5
18
1
Order By: Relevance
“…So it seems that when the SPW 1 can propagate upward in polar latitudes there is no longer the need to do so at lower latitudes. This stronger upward propagation of the SPWs in the northern channel of the PW guide compared to the southern channel is in accordance with the climatology (e.g., Albers et al, 2013).…”
Section: Why Does the Spw 2 Dominate In Period Ii?supporting
confidence: 69%
See 1 more Smart Citation
“…So it seems that when the SPW 1 can propagate upward in polar latitudes there is no longer the need to do so at lower latitudes. This stronger upward propagation of the SPWs in the northern channel of the PW guide compared to the southern channel is in accordance with the climatology (e.g., Albers et al, 2013).…”
Section: Why Does the Spw 2 Dominate In Period Ii?supporting
confidence: 69%
“…In midwinter the PWG is commonly split into a southern and a northern channel (e.g., Dickinson, 1968;Chapman and Miles, 1981;Li et al, 2007). While in the southern channel the SPWs preferably propagate equatorward towards the subtropical zero wind line and barely reach the upper stratosphere (Albers et al, 2013), the northern PWG channel in comparison follows the polar night jet (PNJ) sometimes even reaching up into the mesosphere (Lin, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…16c, f and a, d) but, interestingly, the structure of these temperature and ozone anomalies in the upper stratosphere is less accurate than in the nudged simulation. As well as SSWs influencing ozone, it is also the case that zonally asymmetric ozone can increase the frequency of simulated SSWs (Albers et al, 2013), thus creating the possibility for a feedback in models with interactive chemistry. Figure 15.…”
Section: High Latitudesmentioning
confidence: 99%
“…(3), we use conventional formulae (e.g., Eq. (2) from Albers et al 2013). According to the theory, PWs propagate in atmospheric regions where n 2 m > 0 and should be evanescent in regions where n 2 m < 0.…”
Section: Eliassen-palm Fluxes and Refractivity Indexesmentioning
confidence: 99%
“…Matsuno (1970) introduced the refractive index for PWs and found that the strongest PW propagation is in areas of large positive values of this index. To find out the influence of OGW effects and QBO phases on the PW waveguide, in this study, we use the expression for the quasi-geostrophic zonal mean refractive index squared, n 2 m , for the PW mode with zonal wavenumber m (Andrews et al 1987;Karoly and Hoskins 1982;Li et al 2007;Albers et al 2013):…”
Section: Ogw and Qbo Influence On Planetary Wavesmentioning
confidence: 99%